Integrating Environmental Protection and Sustainable Waste Practices Among the Communities in Higher Education Institutions: Case Study in a Malaysian University - Chan, Siok Sin; Ng, Theam Foo; Hassan, Mohd Sayuti; Ying, Chee Keat; Tan, Mei Lan; Mohd Radzi, Siti Fairuz; Abou Assi, Reem; Chan, Siok-Yee (Frontiers in Environmental Science, 2022)
This work is reporting the advocation of a public Malaysia University for the environmental protection through sustainable waste practices ever since its ban on the use of the “White Coffin” initiative in circa 2008, a flagship for environmental activism on its different campuses targeting to get rid of polystyrene containers. This initiative was not halted but served as a spark of flare for a sustainability journey up to this very day. The effort to realise a sustainable tomorrow as the vision of higher education sector, including the studied Malaysian University has been integrating efforts from various parties. This includes the formation of “Kampus Sejahtera” (wellness campus), regional centre of expertise, sustainability course, and more recently the sustainability month, sustainability network, and most importantly, the local NGO-industrial-academia collaboration in the path toward a sustainable tomorrow. The work in this article delineates a case study in implementing sustainable waste practice from the start to the status, in one of the Malaysian public universities which is ranked 39th in Times Higher Education University in Global Impact Ranking 2021, and top in Malaysia. More emphasis will be placed on the current initiative of the local NGO-industrial-academia collaboration as case study in the midst of the COVID-19 pandemic.